Triglyceride glucose index and mortality in tracheally intubated patients: a MIMIC-IV retrospective cohort study - Weide Lin; Junfan Chen; Feitao Cai (PLoS ONE, 2025)
Tracheal intubation is crucial in ICU treatment but poses risks of complications and mortality. Simple and effective indicators for assessing mortality risk in intubated ICU patients are needed. This study analyzed 5,915 intubated ICU patients from the Medical Information Mart for Intensive Care 3.0 database. Multivariable Cox regression and two-stage linear regression models were used to assess the relationship between triglyceride glucose (TyG) index levels and ICU and in-hospital mortality rates. High TyG levels significantly correlated with increased mortality risk (HR range 1.34–1.44, p < 0.01). The association was linear with ICU mortality but nonlinear with in-hospital mortality. TyG levels ≥9.2 significantly increased in-hospital mortality risk (HR: 1.277, 95% CI: 1.114–1.464, p < 0.001). Higher TyG indices were associated with a higher risk of ICU and in-hospital mortality, emphasizing the importance of these findings for early prevention or timely intervention in intubated ICU patients.